The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1177/154193121005400437
|View full text |Cite
|
Sign up to set email alerts
|

What makes Real-World Interruptions Disruptive? Evidence from an Office Setting

Abstract: With the constant barrage of cell phone calls, emails, instant messages, calendar reminders, and more, interruptions have become a common and consistent occurrence in our daily lives. The majority of the literature on interruptions to date has been based on controlled laboratory experiments and it is not yet completely clear how these results will translate into naturalistic settings and/or if there are certain features of interruptions and resumption that are not observable in the controlled setting. The curr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…The duration of interruption is an important factor that influences resuming processes in terms of both speed and error generation (Altmann & Trafton, 2007). For instance, Hodgetts and Jones (2006) showed interruption duration effects in the Tower of London task but only when using interruptions as short as 3 s. However, these effects were not always confirmed (Cades, Werner, Boehm-Davis, & Arshad, 2010;Einstein, McDaniel, Williford, Pagan, & Dismukes, 2003;Gillie & Broadbent, 1989;Li et al, 2006;Monk et al, 2008). What could explain such discrepancies?…”
Section: Current Unsolved Issues About Factors Influencing Interruptionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The duration of interruption is an important factor that influences resuming processes in terms of both speed and error generation (Altmann & Trafton, 2007). For instance, Hodgetts and Jones (2006) showed interruption duration effects in the Tower of London task but only when using interruptions as short as 3 s. However, these effects were not always confirmed (Cades, Werner, Boehm-Davis, & Arshad, 2010;Einstein, McDaniel, Williford, Pagan, & Dismukes, 2003;Gillie & Broadbent, 1989;Li et al, 2006;Monk et al, 2008). What could explain such discrepancies?…”
Section: Current Unsolved Issues About Factors Influencing Interruptionsmentioning
confidence: 99%
“…It has been shown that interruptions that were similar to the primary task in terms of both modality and task schemata were more impactful than dissimilar ones (Czerwinski et al, 1991). Yet these results do not seem always replicable (Cades et al, 2010;Eyrolle & Cellier, 2000). Lu et al (2013) compiled three meta-analyses to explore the similarity effects using the modality of the tasks.…”
Section: Current Unsolved Issues About Factors Influencing Interruptionsmentioning
confidence: 99%
“…Interruptions to our ongoing mental activities are omnipresent in modern life—whether from cell phones, emails, navigation devices, alarms, etc. An observational study found that people are interrupted an average of 12 times per hour at work in our increasingly digital world (Cades et al, 2010 ), with such interruptions often leading to errors. Another study of nurses from two hospitals showed that interruptions increased both procedural (e.g., fail to check patient identification) and clinical judgment errors (e.g., give the wrong drug or wrong dose), with potentially life threatening consequences (Westbrook et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…As the number of technological devices that people interact with on a daily basis has increased-cell phones, laptops, navigation devices, etc.-so has the incidence of interruptions to ongoing work activities. Recent data has put the frequency of interruptions to as much as 12 times per hour in the workplace (Cades, Werner, Boehm-Davis, & Arshad, 2010), with an estimated productivity cost to companies in the United States of $588 billion per year (Spira & Feintuch, 2005).…”
mentioning
confidence: 99%